Stainless steel material for solid oxide fuel cell and method for manufacturing the same, component for solid oxide fuel cell and solid oxide fuel cell

By controlling the chemical composition and manufacturing process of stainless steel, the problems of reducing conductivity and thermal deformation of solid oxide fuel cells at low temperatures are solved, and the effects of excellent conductivity and thermal deformation suppression are achieved.

CN116490632BActive Publication Date: 2025-03-18NIPPON STEEL STAINLESS STEEL CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180071489.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-14
Filing Date
2021-12-10
Publication Date
2025-03-18
Estimated Expiration
2041-12-10

AI Technical Summary

Technical Problem

At a temperature below 600°C, the conductivity of the solid oxide fuel cell is reduced, and the members are prone to thermal deformation during thinning and lightening.

Method used

By controlling the chemical composition of the stainless steel material, including C, Si, Mn, P, S, Cr, Mo, N, Al, Nb, Ti, Ni, Cu, etc., and using hot rolling and cold rolling manufacturing methods, a stainless steel material with excellent conductivity and thermal deformation is formed.

Benefits of technology

It has achieved a stainless steel material for solid oxide fuel cell with excellent conductivity at a temperature below 600°C and effectively suppressed thermal deformation, and is suitable for low-temperature working solid oxide fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116490632B_ABST
    Figure CN116490632B_ABST
Patent Text Reader

Abstract

A stainless steel material for a solid oxide fuel cell comprises, by mass, C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 22.0-32.0%, Mo: 2.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.40% or less, Ni: 1.00% or less, Cu: 1.00% or less, the effective Cr content represented by the following formula (1) is 24.0-35.0%, and the balance comprises Fe and impurities. Formula (1): Effective Cr content (%) = Cr + 2Mo + 2Si + 5Nb + 2Ti-3 (2C + 3N + Ni + 0.5Mn + 0.2Cu), wherein each element symbol represents the content of each element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a stainless steel material for a solid oxide fuel cell and a method for producing the same, as well as a member for a solid oxide fuel cell and a solid oxide fuel cell. Background Art

[0002] Conventional solid oxide fuel cells (SOFCs) are high-temperature operating types with an operating temperature exceeding 600° C. However, in recent years, low-temperature operating solid oxide fuel cells operating in a temperature range below 600° C. have been proposed (e.g., Patent Documents 1 and 2). Stainless steel is generally used for the components of such solid oxide fuel cells from the perspectives of cost, corrosion resistance, etc.

[0003] Solid oxide fuel cells have been developed mainly as stationary power sources, but in recent years, their use has been expected to expand to various mobile bodies such as business and industrial vehicles, automobiles, and airplanes.

[0004] Prior Art Literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-53388

[0007] Patent Document 2: Japanese Patent No. 6696992 Summary of the invention

[0008] The components constituting a solid oxide fuel cell (e.g., separators, interconnectors, current collectors, etc.) are required to have electrical conductivity. However, since the electrical conductivity of the components decreases as the operating temperature decreases, the electrical conductivity of the components used in conventional high-temperature operating solid oxide fuel cells is sometimes insufficient.

[0009] In addition, when the application is expanded to mobile bodies, the components are required to be thinner and lighter. However, when the components are thinner and lighter, thermal deformation is more likely to occur.

[0010] The present invention has been made to solve the above-mentioned problems, and its object is to provide a stainless steel material for solid oxide fuel cells that has excellent electrical conductivity at a temperature of 600°C or less and can suppress thermal deformation, and a method for manufacturing the same. In addition, the present invention also aims to provide a solid oxide fuel cell component and a solid oxide fuel cell having the stainless steel material for solid oxide fuel cells having such characteristics.

[0011] The present inventors have conducted intensive studies on stainless steel materials and have found that the above-mentioned problems can be solved by controlling the composition to a specific one, thereby completing the present invention.

[0012] That is, the present invention is a stainless steel material for a solid oxide fuel cell, which contains, by mass, C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 22.0-32.0%, Mo: 2.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.40% or less, Ni: 1.00% or less, and Cu: 1.00% or less, wherein the effective Cr content represented by the following formula (1) is 24.0-35.0%, and the balance contains Fe and impurities.

[0013] Effective Cr content (%) = Cr + 2Mo + 2Si + 5Nb + 2Ti-3 (2C + 3N + Ni + 0.5Mn + 0.2Cu) (1)

[0014] In the formula, each element symbol represents the content of each element.

[0015] In addition, the present invention is a method for manufacturing a stainless steel material for a solid oxide fuel cell, wherein a slab is hot rolled and then cold rolled, wherein the slab contains, by mass, C: less than 0.030%, Si: less than 1.00%, Mn: less than 1.00%, P: less than 0.050%, S: less than 0.0030%, Cr: 22.0-32.0%, Mo: less than 2.50%, N: less than 0.030%, Al: less than 0.30%, Nb: less than 0.40%, Ti: less than 0.40%, Ni: less than 1.00%, and Cu: less than 1.00%, wherein the effective Cr amount represented by the following formula (1) is 24.0-35.0%, and the balance contains Fe and impurities.

[0016] Effective Cr content (%) = Cr + 2Mo + 2Si + 5Nb + 2Ti-3 (2C + 3N + Ni + 0.5Mn + 0.2Cu) (1)

[0017] In the formula, each element symbol represents the content of each element.

[0018] Furthermore, the present invention is a member for a solid oxide fuel cell, comprising the above-mentioned stainless steel material for a solid oxide fuel cell.

[0019] Furthermore, the present invention is a solid oxide fuel cell comprising the above-mentioned solid oxide fuel cell member.

[0020] According to the present invention, a stainless steel material for a solid oxide fuel cell having excellent electrical conductivity at a temperature of 600° C. or less and capable of suppressing thermal deformation and a method for manufacturing the same can be provided. In addition, according to the present invention, a solid oxide fuel cell component and a solid oxide fuel cell having the stainless steel material for a solid oxide fuel cell having such characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a schematic plan view of a test piece for measuring conductivity. DETAILED DESCRIPTION

[0022] The embodiments of the present invention are described in detail below. The present invention is not limited to the following embodiments, and it should be understood that within the scope of the present invention, based on the common knowledge of those skilled in the art, the following embodiments may be appropriately modified, improved, etc. and the like, and the solutions obtained are also within the scope of the present invention.

[0023] In addition, in this specification, "%" about a component means mass % unless otherwise specified.

[0024] A stainless steel material for a solid oxide fuel cell according to an embodiment of the present invention (hereinafter referred to as "stainless steel material") has the following composition: C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 22.0-32.0%, Mo: 2.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.40% or less, Ni: 1.00% or less, Cu: 1.00% or less, the effective Cr content represented by the following formula (1) is 24.0-35.0%, and the balance contains Fe and impurities.

[0025] Here, the so-called "impurities" are components (such as unavoidable impurities) mixed in due to various factors such as raw materials such as ores and scraps and manufacturing processes when stainless steel materials are industrially manufactured, and refer to components that are allowed within the range that does not adversely affect the present invention. In addition, the so-called "stainless steel material" is a concept including various shapes such as stainless steel strips, stainless steel plates, and stainless steel foils.

[0026] In addition, the stainless steel material according to the embodiment of the present invention may further contain one or more selected from B: 0.0050% or less, Sn: 0.5% or less, V: 0.5% or less, W: 0.5% or less, Ca: 0.0100% or less, Mg: 0.010% or less, Zr: 0.50% or less, Co: 0.5% or less, Ga: 0.01% or less, Hf: 0.10% or less, and REM: 0.10% or less, as needed.

[0027] <C: 0.030% or less>

[0028] C is an element that affects the electrical conductivity of stainless steel at temperatures below 600°C. If the C content is too high, the electrical conductivity decreases. Therefore, the C content is set to 0.030% or less, preferably 0.020% or less, and more preferably 0.015% or less. On the other hand, the lower limit of the C content is not particularly limited, but the lower the C content, the more time the refining process takes, and the manufacturing cost may increase. Therefore, the C content is preferably 0.0002% or more, and more preferably 0.0005% or more.

[0029] <Si: 1.00% or less>

[0030] Si is an element that improves the heat resistance of stainless steel and is effective in suppressing the formation of Cr oxide film at temperatures below 600°C and obtaining thermal deformation. However, if the Si content is too high, a continuous oxide of SiO2 is generated at the interface of the stainless steel, thereby reducing the conductivity, and the toughness may be reduced due to hardening. Therefore, the Si content is set to 1.00% or less, preferably 0.80% or less, more preferably 0.60% or less, and further preferably 0.30% or less. On the other hand, the lower limit of the Si content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Si, the Si content is preferably 0.05% or more, and more preferably 0.08% or more.

[0031] <Mn: 1.00% or less>

[0032] Mn is an element that improves the toughness of stainless steel and is effective in improving the conductivity of the oxide film by forming (Mn, Cr)3O4 type oxides. However, if the Mn content is too high, the heat resistance and the effect of suppressing thermal deformation may be reduced. Therefore, the Mn content is set to 1.00% or less, preferably 0.50% or less. On the other hand, the lower limit of the Mn content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Mn, the Mn content is preferably 0.05% or more, and more preferably 0.08% or more.

[0033] <P: 0.050% or less>

[0034] P is an element that may reduce the toughness of stainless steel. Therefore, the P content is set to 0.050% or less, preferably 0.040% or less. On the other hand, there is no particular lower limit for the P content, but the lower the P content, the more time is required for the refining process, and the manufacturing cost may increase. Therefore, the P content is preferably 0.001% or more, and more preferably 0.010% or more.

[0035] <S: 0.0030% or less>

[0036] S is an element that generates sulfide-based inclusions and has the potential to reduce the power generation efficiency of SOFC by evaporating and poisoning the electrode. Therefore, the S content is set to 0.0030% or less, preferably 0.0015% or less. On the other hand, the lower limit of the S content is not particularly limited, but the lower the S content, the more time is required for the refining process, and the manufacturing cost may increase. Therefore, the S content is preferably 0.0001% or more, and more preferably 0.0002% or more.

[0037] <Cr:22.0~32.0%>

[0038] Cr is a main element for forming a passive film on the surface of stainless steel, and can improve the corrosion resistance, heat resistance and other characteristics by the passive film. From the viewpoint of forming a Cr oxide film with excellent conductivity at a temperature below 600°C and obtaining the effect of suppressing thermal deformation, the Cr content is set to 22.0% or more, preferably 22.5% or more. On the other hand, if the Cr content is too high, the toughness and other characteristics are reduced, so the Cr content is 32.0% or less, preferably 31.0% or less.

[0039] <Mo: 2.50% or less>

[0040] Mo is a main element for strengthening the passive film of stainless steel, and can improve the characteristics such as corrosion resistance and heat resistance through the passive film. In addition, Mo is also an element that promotes the formation of Cr oxide film of stainless steel at a temperature below 600°C to improve conductivity, and reduces the thermal expansion coefficient to give the effect of inhibiting thermal deformation. Generally, Cr oxide generated at a temperature below 600°C contains Fe, so the conductivity is low, but by making Mo exist in Cr oxide, the conductivity can be improved. However, if the Mo content is too much, it is possible to damage the toughness and the effect of inhibiting thermal deformation due to hardening. Therefore, the Mo content is set to 2.50% or less, preferably 2.00% or less, and more preferably 1.50% or less. On the other hand, the lower limit of the Mo content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Mo, the Mo content is preferably 0.05% or more, and more preferably 0.30% or more.

[0041] <N: 0.030% or less>

[0042] N is an element that combines with Al to form AlN, which is the starting point of abnormal oxidation, and may reduce the toughness of stainless steel. Therefore, the N content is set to 0.030% or less, preferably 0.025% or less. On the other hand, the lower limit of the N content is not particularly limited, but the lower the N content, the more time the refining process takes, and the manufacturing cost may increase. Therefore, the N content is preferably 0.001% or more, and more preferably 0.010% or more.

[0043] <Al: 0.30% or less>

[0044] Al is an element that promotes the formation of Cr oxide film of stainless steel at a temperature below 600°C, thereby effectively improving the conductivity. However, if the Al content is too much, it becomes easy to generate AlN, which becomes the starting point of abnormal oxidation, and it is possible to damage the toughness and thermal deformation suppression effect of the stainless steel. Therefore, the Al content is set to 0.30% or less, preferably 0.25% or less. On the other hand, the lower limit of the Al content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Al, the Al content is preferably 0.01% or more, and more preferably 0.03% or more.

[0045] <Nb: 0.40% or less>

[0046] Nb, like Ti, preferentially combines with C and N to form Nb carbonitrides, and is therefore an element that increases the effective Cr content of stainless steel. Therefore, Nb promotes the formation of Cr oxide film at temperatures below 600°C, which helps to improve conductivity. However, if the Nb content is too high, the amount of solid-solution Nb that is not consumed in the formation of Nb carbonitrides increases. As a result, the toughness and thermal deformation suppression effects may be impaired due to hardening. Therefore, the Nb content is set to less than 0.40%, preferably less than 0.35%. On the other hand, the lower limit of the Nb content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Nb, the Nb content is preferably 0.01% or more, and more preferably 0.05% or more.

[0047] <Ti: 0.40% or less>

[0048] Ti, like Nb, preferentially combines with C and N to form Ti carbonitrides, and is therefore an element that increases the effective Cr content of stainless steel. Therefore, Ti promotes the formation of Cr oxide films at temperatures below 600°C, contributing to improved conductivity. However, if the Ti content is too high, the Ti carbonitrides coarsen, which becomes a starting point, and the effect of suppressing toughness and thermal deformation decreases. Therefore, the Ti content is set to 0.40% or less, preferably 0.35% or less. On the other hand, the lower limit of the Ti content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Ti, the Ti content is preferably 0.01% or more, and more preferably 0.05% or more.

[0049] The total content of Nb and Ti is not particularly limited, but is preferably 0.32% or more, and more preferably 0.35% or more. In addition, the ratio of the Nb content to the Ti content (Nb content / Ti content) is not particularly limited, but is preferably 1.0 or less, and more preferably 0.9 or less. By controlling the contents of Nb and Ti to such conditions, the effect of the present invention can be stably obtained.

[0050] <Ni: 1.00% or less>

[0051] Ni is an element that improves the corrosion resistance of stainless steel and suppresses the reduction of toughness. However, since Ni is an austenite phase stabilizing element, if the Ni content is too much, the thermal expansion coefficient increases and the inhibitory effect of thermal deformation decreases. Therefore, the Ni content is set to 1.00% or less, preferably 0.80% or less. On the other hand, the lower limit of the Ni content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Ni, the Ni content is preferably 0.01% or more, and more preferably 0.05% or more.

[0052] <Cu: 1.00% or less>

[0053] Cu is an element that improves the corrosion resistance and electrical conductivity of stainless steel. However, since Cu is an austenite phase stabilizing element, if the Cu content is too much, the thermal expansion coefficient increases and the effect of suppressing thermal deformation decreases. Therefore, the Cu content is set to 1.00% or less, preferably 0.80% or less. On the other hand, the lower limit of the Cu content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Cu, the Cu content is preferably set to 0.01% or more, and more preferably 0.03% or more.

[0054] <Effective Cr content: 24.0~35.0%>

[0055] The effective Cr amount is represented by the following formula (1).

[0056] Effective Cr content (%) = Cr + 2Mo + 2Si + 5Nb + 2Ti-3 (2C + 3N + Ni + 0.5Mn + 0.2Cu) (1)

[0057] In the formula, each element symbol represents the content of each element. In addition, "Cr+2Mo+2Si+5Nb+2Ti" represents Cr equivalent, and "2C+3N+Ni+0.5Mn+0.2Cu" represents Ni equivalent.

[0058] If the effective Cr content is too much, intermetallic compounds of the σ phase or the like will precipitate at 400-600°C, the toughness will be reduced, and the Cr content will be consumed by intermetallic compounds, carbonitrides, etc., thus reducing the conductivity. As a result, the electrical conductivity is reduced, and the thermal deformation suppression effect is reduced due to the appearance of intermetallic compounds with deformation ability different from that of the parent phase. Therefore, the effective Cr content is set to 35.0% or less, preferably 32.0% or less. On the other hand, if the effective Cr content is too low, the Cr equivalent becomes less than the Ni equivalent, thereby impairing the formation of the Cr oxide film and reducing the electrical conductivity, and reducing the thermal deformation suppression characteristics due to the increase in the thermal expansion coefficient. Therefore, the effective Cr content is set to 24.0% or more, preferably 25.0% or more.

[0059] <B: 0.0050% or less>

[0060] B is an element that increases the grain boundary strength by preferentially concentrating at the grain boundary, and is effective in improving secondary workability, and is included in stainless steel materials as needed. However, if the B content is excessive, the boride (Cr2B) at the grain boundary will coarsen, thereby reducing the effect of suppressing hot deformation. Therefore, the B content is set to 0.0050% or less, preferably 0.0030% or less. On the other hand, the lower limit of the B content is not particularly limited. From the viewpoint of obtaining the effect brought by B, the B content is preferably 0.0002% or more, and more preferably 0.0005% or more.

[0061] <Sn: 0.5% or less>

[0062] Sn is an element effective in improving corrosion resistance and electrical conductivity, and is included in stainless steel materials as required. However, if the Sn content is too much, hot workability and toughness will decrease. Therefore, the Sn content is set to 0.5% or less, preferably 0.3% or less. On the other hand, the lower limit of the Sn content is not particularly limited. From the viewpoint of obtaining the effect brought about by Sn, the Sn content is preferably 0.01% or more, and more preferably 0.05% or more.

[0063] <V: 0.5% or less>

[0064] V is an element that improves the strength without damaging the toughness of stainless steel, and is included in stainless steel as needed. However, if the V content is too much, the workability and toughness may be reduced, and the cost will increase. Therefore, the V content is set to 0.5% or less, preferably 0.4% or less. On the other hand, the lower limit of the V content is not particularly limited. From the viewpoint of obtaining the effect brought by V, the V content is preferably 0.01% or more, and more preferably 0.05% or more.

[0065] <W: 0.5% or less>

[0066] W is an element that improves the strength without damaging the toughness of stainless steel, and is contained in stainless steel as needed. However, if the W content is too high, workability and toughness may be reduced, and the cost will increase. Therefore, the W content is set to 0.5% or less, preferably 0.4% or less. On the other hand, the lower limit of the W content is not particularly limited. From the viewpoint of obtaining the effect brought by W, the W content is preferably 0.01% or more, and more preferably 0.05% or more.

[0067] <Ca: 0.0100% or less>

[0068] Ca is an element that fixes S to improve oxidation resistance and promotes the formation of Cr oxide film, and is included in stainless steel materials as needed. However, if the Ca content is too high, the amount of inclusions generated increases, which reduces the electrical conductivity and thermal deformation suppression characteristics. Therefore, the Ca content is set to 0.0100% or less, preferably 0.0050% or less. On the other hand, the lower limit of the Ca content is not particularly limited. From the viewpoint of obtaining the effect brought about by Ca, the Ca content is preferably 0.0005% or more, and more preferably 0.0010% or more.

[0069] <Mg: 0.010% or less>

[0070] Mg is an element effective for refining stainless steel and is contained in stainless steel as required. However, if the Mg content is too high, the amount of inclusions generated increases, which reduces the effect of suppressing conductivity and thermal deformation. Therefore, the Mg content is set to 0.010% or less, preferably 0.005% or less. On the other hand, the lower limit of the Mg content is not particularly limited. From the viewpoint of obtaining the effect brought about by Mg, the Mg content is preferably 0.0001% or more, and more preferably 0.0005% or more.

[0071] <Zr: 0.50% or less>

[0072] Zr is an element that fixes C and increases the effective Cr content of stainless steel, and is contained in stainless steel as needed. However, if the Zr content is too high, the workability of the stainless steel is reduced. Therefore, the Zr content is set to 0.50% or less, preferably 0.40% or less. On the other hand, the lower limit of the Zr content is not particularly limited. From the viewpoint of obtaining the effect brought by Zr, the Zr content is preferably 0.001% or more, and more preferably 0.005% or more.

[0073] <Co: 0.5% or less>

[0074] Co is an element that improves the strength without damaging the toughness of stainless steel, and is included in stainless steel as needed. However, if the Co content is too much, the workability and toughness may be reduced, and the cost will increase. Therefore, the Co content is set to 0.5% or less, preferably 0.4% or less. On the other hand, the lower limit of the Co content is not particularly limited. From the viewpoint of obtaining the effect brought by Co, the Co content is preferably 0.01% or more, and more preferably 0.05% or more.

[0075] <Ga: 0.01% or less>

[0076] Ga is an element that improves the hot workability of stainless steel and is contained in stainless steel as needed. However, if the Ga content is too much, the manufacturability is reduced. Therefore, the Ga content is set to 0.01% or less, preferably 0.005% or less. On the other hand, the lower limit of the Ga content is not particularly limited. From the viewpoint of obtaining the effect brought by Ga, the Ga content is preferably 0.0001% or more, more preferably 0.0005% or more.

[0077] <Hf: 0.10% or less>

[0078] Hf is an element that fixes C and increases the effective Cr content of stainless steel, and is contained in stainless steel as needed. However, if the Hf content is too high, the workability of the stainless steel is reduced. Therefore, the Hf content is set to 0.10% or less, preferably 0.08% or less. On the other hand, the lower limit of the Hf content is not particularly limited. From the viewpoint of obtaining the effect brought about by Hf, the Hf content is preferably 0.001%, and more preferably 0.005%.

[0079] <REM: 0.10% or less>

[0080] REM (rare earth element) preferentially combines with S and P to form a compound, so it is possible to suppress the reduction in conductivity and thermal deformation suppression effect caused by S and P. REM is contained in stainless steel materials as needed. However, if the REM content is too much, the stainless steel material will harden, and the toughness and processability may be reduced. Therefore, the REM content is set to less than 0.10%, preferably less than 0.08%. On the other hand, the lower limit of the REM content is not particularly limited. From the viewpoint of obtaining the effect brought about by REM, the REM content is preferably 0.001% or more, and more preferably 0.005% or more.

[0081] Furthermore, REM is a general term for two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). They can be used alone or in the form of a mixture. Among REM, La and Y are preferred.

[0082] In the stainless steel material according to the embodiment of the present invention, the crystal orientation ratio ({211} / {200}) of the crystal orientation {211} to the crystal orientation {200} at a depth of 10 μm from the surface is preferably greater than 1.5 and less than 3.5, more preferably 2.0 to 3.0.

[0083] The electrical conductivity of stainless steel at temperatures below 600°C mainly depends on the Cr concentration of the Cr oxide film ((Cr, Fe)2O3) on the surface of the stainless steel. By controlling the crystal orientation ratio ({211} / {200}) within the above range, the orientation of the base material and the Cr oxide film is improved, and the Cr concentration of the surface layer ((Cr, Fe)2O3) can be increased, thereby improving the electrical conductivity at temperatures below 600°C.

[0084] Here, the above-mentioned crystal orientation is obtained by X-ray diffraction of the surface of the stainless steel material. Specifically, the stainless steel material is cut and the crystal orientation is measured on its surface using an X-ray diffraction device (RINT 2500 manufactured by Rigaku Co., Ltd.). For example, a copper tube ball is used, and the characteristic X-rays (wavelength (λ) = 1.5444 angstroms) of CuKα emitted therefrom are used for diffraction. In this case, in the 2θ method, {200} is detected at 65.20° and {211} is detected at 82.58°, so the X-ray intensity ratio of these crystal planes is calculated.

[0085] In the stainless steel material according to the embodiment of the present invention, at the center position in the thickness direction (the position of t / 2 when the thickness of the stainless steel material is t), the crystal orientation ratio ({211} / {200}) of the crystal orientation {211} to the crystal orientation {200} is preferably greater than 0.5 and less than 2.0, and more preferably 0.5 to 1.5.

[0086] The thermal deformation of the stainless steel material is affected by the linear expansion coefficient and Young's modulus at the center of the thickness direction. Therefore, by controlling the crystal orientation ratio within the above range, the linear expansion coefficient and Young's modulus are reduced, thereby suppressing the thermal deformation.

[0087] Here, the above-mentioned crystal orientation is obtained by grinding (reducing) the surface of the stainless steel material to t / 2 and performing X-ray diffraction on the surface. The X-ray diffraction can be performed in the same manner as described above.

[0088] The shape of the stainless steel material according to the embodiment of the present invention is not particularly limited, but is preferably in the form of a plate or foil. When the stainless steel material is in the form of a plate or foil, its thickness is, for example, 0.1 to 5.0 mm, preferably 0.1 to 3.0 mm, more preferably 0.1 to 1.0 mm, and further preferably 0.1 to 0.5 mm.

[0089] The stainless steel material according to the embodiment of the present invention can be produced by a known method except that a slab having the above-mentioned composition is used.

[0090] Here, an example of a typical method for producing a stainless steel material according to an embodiment of the present invention will be described. In addition, the method for producing a stainless steel material according to an embodiment of the present invention is not limited to the following method.

[0091] The stainless steel material according to the embodiment of the present invention can be produced by hot rolling a steel billet having the above-mentioned composition and then cold rolling the steel billet. The conditions for hot rolling and cold rolling are not particularly limited and may be appropriately adjusted according to the composition.

[0092] Preferably, the hot rolled material obtained by hot rolling is pickled before cold rolling, and then surface grinding is performed. In addition, it is preferred that the hot rolled material is pickled without annealing. By setting such conditions, it becomes easy to control the crystal orientation of the stainless steel material within the above range.

[0093] The surface grinding method is not particularly limited, and can be performed using, for example, a coil grinder. In this case, the particle size of the grinder may be #120 to 600. The thickness of the surface grinding is not particularly limited, but may be 0.005 to 0.100 mm.

[0094] After the cold rolling, known steps such as annealing and pickling may be performed.

[0095] The stainless steel material according to the embodiment of the present invention manufactured as described above forms a passive film on the surface in an oxygen-containing atmosphere (e.g., air atmosphere). The passive film has excellent conductivity at a temperature below 600°C. In addition, the stainless steel material is also difficult to be thermally deformed, and is therefore suitable for use in solid oxide fuel cells, particularly low-temperature solid oxide fuel cells that operate in a temperature range below 600°C (e.g., 500 to 600°C).

[0096] When the stainless steel material according to the embodiment of the present invention is used in a solid oxide fuel cell, the stainless steel material can be used for components such as separators, current collectors (e.g., air electrode current collectors and fuel electrode current collectors), interconnectors, bus bars, end plates, fuel electrode frames, etc. Among these components, the stainless steel material according to the embodiment of the present invention is preferably used for one or more components selected from separators, interconnectors, and current collectors.

[0097] A solid oxide fuel cell member according to an embodiment of the present invention includes a stainless steel material according to an embodiment of the present invention. In addition, a solid oxide fuel cell according to an embodiment of the present invention includes a solid oxide fuel cell member according to an embodiment of the present invention.

[0098] The solid oxide fuel cell member is not particularly limited, and examples thereof include the various members described above.

[0099] The stainless steel material can be appropriately processed in shape according to the shapes of various components. In addition, a conductive coating can also be formed on the surface of the stainless steel material. The conductive coating is not particularly limited and can be formed from materials known in the technical field. For example, the conductive coating can be formed using metals with excellent conductivity such as Ag and Co. In addition, the conductive coating can be a layer of a single metal or a layer of an alloy, and can be a single-layer structure or a stacked structure.

[0100] Furthermore, from the viewpoint of improving the adhesion with the conductive coating, the stainless steel material may also be subjected to modification (roughening) of the passive film. For example, modification (roughening) of the passive film may be performed by a known method such as immersing the stainless steel material in a fluorine-nitric acid solution.

[0101] Example

[0102] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these examples.

[0103] The slabs of the composition shown in Table 1 were melted and hot-rolled to form a hot-rolled plate with a thickness of 3.5 mm, then pickled without annealing, and surface ground by 0.05 mm using a coil mill (grain size number 120). Next, the hot-rolled plate after surface grinding was cold-rolled to form a cold-rolled plate with a thickness of 0.1 to 0.6 mm, and then annealed and pickled to obtain a stainless steel material. The stainless steel materials manufactured by this method are indicated in Table 2 as "without" hot-rolled plate annealing and "with" surface grinding.

[0104] In addition, stainless steel was produced under the same conditions except that the surface grinding was not performed in the above-mentioned production method. The stainless steel material produced by this method is shown in Table 2 as “without” hot-rolled sheet annealing and “without” surface grinding.

[0105] In addition, the following stainless steel materials were also manufactured, which were obtained by hot rolling under the same conditions as above to form hot-rolled plates, annealing at 950-1050°C, pickling, surface grinding and cold rolling. The stainless steel materials manufactured by this method are shown in Table 2 as "with" hot-rolled plate annealing and "with" surface grinding.

[0106] Table 1

[0107]

[0108] Next, for the obtained stainless steel material, the crystal orientations {200} and {211} at a depth of 10 μm from the surface and at the center of the thickness direction were measured to obtain the crystal orientation ratio ({211} / {200}). The crystal orientation was measured under the above conditions. The results are shown in Table 2.

[0109] The obtained stainless steel material was also evaluated for electrical conductivity and thermal deformation. The evaluation method was as follows.

[0110] (1) Electrical conductivity

[0111] The stainless steel material was immersed in an aqueous solution (liquid temperature 60° C.) containing 5.0 mass % hydrofluoric acid and 15 mass % nitric acid for 1 to 5 minutes to perform surface modification, and then subjected to coating treatment to form a conductive coating. During the coating treatment, adjustment was made so that a Co plating layer was formed on the surface of the surface-modified stainless steel material with a thickness of 2 to 5 μm.

[0112] Two pieces of stainless steel materials with conductive coatings (hereinafter referred to as "stainless steel materials with conductive coatings") were exposed to heat at 600°C for 1000 hours in an atmosphere (dew point 20°C; H2O concentration of about 2.31%), and then used to prepare the following Figure 1The test piece for measurement shown above was measured by a four-terminal method using a potentiostat. Specifically, the measurement was performed as follows.

[0113] First, a conductive paste (Ag paste) was applied to the center of two sheets of stainless steel materials 10 with conductive coating in a square shape (10 mm on one side, 10 μm thick), and dried to form a conductive portion 20. Next, the conductive portions 20 of the two sheets of stainless steel materials 10 with conductive coating were overlapped and arranged in a cross shape, and then sandwiched between alumina plates, a weight (200 g) was placed, and the conductive portion 20 was sintered in an electric furnace (850°C × 30 minutes). Next, a small cutter was used to cut the surface until the metal base material was exposed, forming a conductive portion 20. Figure 1 Next, the silver wire 40 It is wound around the wiring installation part 30, coated with conductive paste, and dried at 150°C for 30 minutes to obtain a test piece for measurement. Next, the test piece for measurement is placed in a high-temperature electrochemical measurement device, and the voltage-current curve is obtained by a four-terminal method using a constant potential meter. In this measurement, the measurement temperature is set to 600°C, and the voltage is scanned until 10mV. In addition, the resistance value is calculated from the slope of the voltage-current curve. In this evaluation, the resistance value is set to 20mΩ·cm 2 The following cases were judged as A (particularly excellent high temperature conductivity), and the resistance value exceeded 20 mΩ·cm 2 and 30mΩ·cm 2 The following cases were judged as B (excellent high temperature conductivity), and the resistance value exceeded 30 mΩ·cm 2 The case was judged as C (insufficient high temperature conductivity).

[0114] (2) Thermal deformation

[0115] The thermal deformation of stainless steel was evaluated using the high-temperature bending strength test method specified in JIS R1604:2008. Specifically, a 3-point bending method with a distance between external fulcrums of 30 mm was used, and the stainless steel was cut to prepare a 4 mm × 40 mm test piece. Next, the test piece and the 3-point bending tester were placed in a muffle furnace, and after heating to 650°C in the atmosphere, the bending strength of the test piece that produced thermal deformation was measured. The case where the bending strength was above 150 MPa was judged as A (high thermal deformation suppression effect), and the case where the bending strength was less than 150 MPa was judged as C (low thermal deformation suppression effect).

[0116] Table 2 shows the above-mentioned evaluation results.

[0117] Table 2

[0118]

[0119] As shown in Table 2, the stainless steel materials of Test No. 1 to 14 (Examples of the present invention) have excellent electrical conductivity and high thermal deformation suppression effect because they have a predetermined composition. In particular, the stainless steel materials of Test No. 2, 7, 12 and 13 have a preferred composition and omit hot-rolled sheet annealing, so the crystal orientation ratio is in a particularly preferred range and the electrical conductivity is very good. In addition, the comparison between Test No. 2 and 3 confirms the following tendency: by performing surface grinding, the crystal orientation ratio at a depth of 10 μm from the surface is in a preferred range, and the electrical conductivity is improved.

[0120] In contrast, the stainless steel materials of Test Nos. 15 to 21 (Comparative Examples) have compositions or effective Cr amounts outside the prescribed ranges, and therefore, even if hot-rolled sheet annealing is omitted to provide an appropriate crystal orientation, one or both of the electrical conductivity and the effect of suppressing thermal deformation are insufficient.

[0121] As can be seen from the above results, according to the present invention, it is possible to provide a stainless steel material for solid oxide fuel cells that has excellent electrical conductivity at a temperature of 600°C or less and can suppress thermal deformation, and a method for manufacturing the same. In addition, according to the present invention, it is possible to provide a solid oxide fuel cell component and a solid oxide fuel cell having the stainless steel material for solid oxide fuel cells having such characteristics.

[0122] Description of Reference Numerals

[0123] 10Stainless steel with conductive coating

[0124] 20 Conductive part

[0125] 30 Wiring installation department

[0126] 40 Silver Line

Claims

1. A stainless steel material for a solid oxide fuel cell, comprising, by mass, C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 22.0-32.0%, Mo: 2.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.01-0.40%, Ni: 0.01-1.00%, Cu: 0.01-1.00%, an effective Cr content represented by the following formula (1) being 24.0-35.0%, and the balance being Fe and impurities, Effective Cr content (%) = Cr + 2Mo + 2Si + 5Nb + 2Ti-3 (2C + 3N + Ni + 0.5Mn + 0.2 Cu) ··· (1) In the formula, each element symbol represents the content of each element.

2. The stainless steel material for a solid oxide fuel cell according to claim 1, further comprising, by mass, one or more selected from the group consisting of B: 0.0050% or less, Sn: 0.5% or less, V: 0.5% or less, W: 0.5% or less, Ca: 0.0100% or less, Mg: 0.010% or less, Zr: 0.50% or less, Co: 0.5% or less, Ga: 0.01% or less, Hf: 0.10% or less, and REM: 0.10% or less.

3. The stainless steel material for a solid oxide fuel cell according to claim 1 or 2, wherein at a depth of 10 μm from the surface, a crystal orientation ratio of the crystal orientation {211} to the crystal orientation {200}, that is, {211} / {200}, exceeds 1.5 and is less than 3.

5.

4. The stainless steel material for a solid oxide fuel cell according to claim 1 or 2, wherein at the center portion in the thickness direction, a crystal orientation ratio of {211} to {200}, that is, {211} / {200}, is greater than 0.5 and less than 2.

0.

5. The stainless steel material for a solid oxide fuel cell according to claim 1 or 2, which is used for one or more members selected from the group consisting of a separator, an interconnector, and a current collector.

6. A method for producing a stainless steel material for a solid oxide fuel cell, comprising hot rolling a slab and then cold rolling the slab, wherein the slab comprises, by mass, C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 22.0-32.0%, Mo: 2.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.01-0.40%, Ni: 0.01-1.00%, Cu: 0.01-1.00%, an effective Cr content represented by the following formula (1) is 24.0-35.0%, and the balance is Fe and impurities, Effective Cr content (%) = Cr + 2Mo + 2Si + 5Nb + 2Ti-3 (2C + 3N + Ni + 0.5Mn + 0.2 Cu) ··· (1) In the formula, each element symbol represents the content of each element.

7. The method for producing a stainless steel material for a solid oxide fuel cell according to claim 6, wherein the slab further contains, by mass, one or more selected from the group consisting of B: 0.0050% or less, Sn: 0.5% or less, V: 0.5% or less, W: 0.5% or less, Ca: 0.0100% or less, Mg: 0.010% or less, Zr: 0.50% or less, Co: 0.5% or less, Ga: 0.01% or less, Hf: 0.10% or less, and REM: 0.10% or less.

8. The method for producing a stainless steel material for a solid oxide fuel cell according to claim 6 or 7, wherein before the cold rolling, the hot-rolled material obtained by the hot rolling is pickled and then surface-ground. 9 . The method for producing a stainless steel material for a solid oxide fuel cell according to claim 8 , wherein the hot rolled material is pickled without being annealed. 10 . A member for a solid oxide fuel cell, comprising the stainless steel material for a solid oxide fuel cell according to claim 1 . 11 . A solid oxide fuel cell comprising the solid oxide fuel cell member according to claim 10 .

Citation Information

Patent Citations

  • Fuel cell system and operation method therefor and electrochemical system

    JP2020053388A

  • Ferritic stainless steel sheet and method for producing ferritic stainless steel sheet with oxide coating film having excellent conductivity and adhesion

    CN104379790A